UTILIZING SMARTPHONE AS A FUN MEDIA TO ENHANCE THE STUDENTS’ ENGLISH CAPABILITY - Fatihatun Cahyaning Tyas; Muhammad Ulinnu (Universitas Negeri Padang, 2013)
Many students in Indonesia are using Smartphones such as blackberry, android and iOS. But many of the students are not fully utilize the applications in Smartphone to support their English learning. In Smartphone, there is Google store which is a service from Google that provides English dictionary application and other English applications that student can use for learning English. From this point, students who cannot escape from their Smartphone would be productive if they are able to take advantage of English learning applications. Therefore, utilizing the Smartphone as a fun learning media is one way of students to enhance their English capability relaxively and fun. The use of this method is expected to be a special strategy for students who already cannot get away from their gadgets and Smartphone to be able to learn and enhance their English capability. This presentation aims to report the results of investigating study in the use of Smartphone as a fun media to help enhance English capability in students through English applications. A review of the literature on language teaching using the Smartphone as a fun media will be reviewed. Finally, the presentation will discuss how the role of Smartphone in the process of learning English.